2021
DOI: 10.3390/cancers13246241
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes after International Referral of Uveal Melanoma Patients for Proton Therapy

Abstract: Objective: To assess oncological and ophthalmological outcomes after international referral of uveal melanoma patients for proton therapy. Materials and Methods: This is a retrospective study among Dutch uveal melanoma patients who were treated in Switzerland with 60.0 CGE proton therapy (in 4 fractions) from 1987 to 2019. All patients were ineligible for brachytherapy due to tumour size and/or proximity to the optic nerve. Time-to-event analyses were performed using Kaplan–Meier’s methodology and Cox proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Given the heterogeneity of UM, also in terms of perfusion, an analysis which separately evaluates these distinct tumour parts might be more appropriate [ 30 ]. Furthermore, in accordance with the high rates of local control of 95% and 94% for ruthenium brachytherapy and PBT respectively [ 36 , 37 ], no recurrences were present in our cohort. A study with a longer follow-up is therefore warranted to determine if the observed biomarkers of therapy response are also indicative of a good response with no local recurrences on the longer term.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Given the heterogeneity of UM, also in terms of perfusion, an analysis which separately evaluates these distinct tumour parts might be more appropriate [ 30 ]. Furthermore, in accordance with the high rates of local control of 95% and 94% for ruthenium brachytherapy and PBT respectively [ 36 , 37 ], no recurrences were present in our cohort. A study with a longer follow-up is therefore warranted to determine if the observed biomarkers of therapy response are also indicative of a good response with no local recurrences on the longer term.…”
Section: Discussionsupporting
confidence: 87%
“…Patients were included in the study between March 2019 and March 2021. Following national guidelines, patients with small to intermediate-sized choroidal melanomas with a tumour prominence ≤ 7 mm and basal diameters ≤ 16 mm were considered eligible for ruthenium-106 brachytherapy, while larger tumours and juxtapapillary located tumours were referred for PBT at the HollandPTC (Delft, the Netherlands) [ 36 ]. For patients treated with brachytherapy, the dose to the tumour apex was 130 Gy, with a maximum scleral dose of 1000 Gy, as described by Marinkovic et al [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although the benefit of including MRI in radiotherapy planning requires further study, we expect less benefit for patients treated with brachytherapy, due to the limited degrees of freedom with the currently available applicators. For PBT, however, the currently relatively large margins of up to 3 mm are in part needed for the uncertainties introduced by the ultrasound measurements [47] , [48] , [49] . Given the earlier reported benefits of including MRI for ocular PBT planning, we would recommend to perform an MRI for these patients and use the proposed 3D prominence and basal diameter definitions to resolve the discrepancies observed for complexly shaped tumours between MRI and ultrasound [25] , especially until fully image-based 3D treatment planning systems for UM are clinically available [21] , [50] , [51] , [52] .…”
Section: Discussionmentioning
confidence: 99%
“… 4 Currently, the tumor location and extent in ocular proton beam therapy are primarily modeled using tantalum clips and surgical measurements. 32 One of the steps toward clipless treatment would be to use fundus photographs to determine the tumor location relative to the macula. We assessed the impact of the varying scale of fundus images for a patient with an apparent 12.5-mm tumor–macula distance ( Fig.…”
Section: Methodsmentioning
confidence: 99%